2012
DOI: 10.1242/jcs.099184
|View full text |Cite
|
Sign up to set email alerts
|

The SEC6 protein is required for function of the contractile vacuole inChlamydomonas reinhardtii

Abstract: SummaryContractile vacuoles (CVs) are essential for osmoregulation in many protists. To investigate the mechanism of CV function in Chlamydomonas, we isolated novel osmoregulatory mutants. Four of the isolated mutant cell lines carried the same 33,641 base deletion, rendering the cell lines unable to grow under strong hypotonic conditions. One mutant cell line (Osmo75) was analyzed in detail. The CV morphology was variable in mutant cells, and most cells had multiple small CVs. In addition, one or two enlarged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 60 publications
(75 reference statements)
2
31
0
Order By: Relevance
“…As KCN11 was localized to the contractile vacuole membrane, we examined the contractile vacuole functional properties of the cells. In the growth medium, the average contractile vacuole periods between wild-type (WT) cells and kcn11 mutants were similar, with 20.72±0.53 s (mean±s.e.m., n=45) for WT cells and 20.43±0.51 s (n=45) for the mutants, which are consistent with previous report (Komsic-Buchmann et al, 2012) ( Fig. 4A,B).…”
Section: Kcn11 Controls Contractile Vacuole Cycle and Functions Durinsupporting
confidence: 93%
See 3 more Smart Citations
“…As KCN11 was localized to the contractile vacuole membrane, we examined the contractile vacuole functional properties of the cells. In the growth medium, the average contractile vacuole periods between wild-type (WT) cells and kcn11 mutants were similar, with 20.72±0.53 s (mean±s.e.m., n=45) for WT cells and 20.43±0.51 s (n=45) for the mutants, which are consistent with previous report (Komsic-Buchmann et al, 2012) ( Fig. 4A,B).…”
Section: Kcn11 Controls Contractile Vacuole Cycle and Functions Durinsupporting
confidence: 93%
“…During diastole of the contractile vacuole cycle, liquid-filled vesicles continue to fuse with the contractile vacuole Komsic-Buchmann et al, 2012;Luykx et al, 1997;Parkinson et al, 2014). Vesicle fusion requires the function of the exocyst because contractile vacuole formation is compromised in a sec6 mutant in C. reinhardtii (Komsic-Buchmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cerevisiae Vtc1p is present in a complex that is involved in acidocalcisome membrane fusion events and polyphosphate synthesis (Ogawa et al, 2000;Uttenweiler et al, 2007;Hothorn et al, 2009), while S. cerevisiae Vtc4p is a polyphosphate polymerase (Hothorn et al, 2009). Other proteins associated with various vacuole types have been analyzed through mutational studies and shown to be involved in contractile vacuole function, autophagy, cytokinesis, and lysosomal inactivation of Parainfluenza virus (Komsic-Buchmann et al, 2012;Ding et al, 2014;Tenenboim et al, 2014). The Vtc proteins of S. cerevisiae appear to assemble into a complex whose formation requires all of the polypeptide subunits of the complex.…”
Section: Structure and Function Of Vtc1mentioning
confidence: 99%